Disorders of menstruation - Marshburn, Paul B.; Hurst, Bradley S.; Wiley InterScience (Online service) (Chichester, West Sussex : John Wiley & Sons, 2011)
Learn how to interpret menstrual cycle events as vital signs for women. Irregularities in the pattern and amount of vaginal bleeding of uterine origin are often signs of pathology or an aberration in the function of the hypothalamic, pituitary, and ovarian system. The type of menstrual disorder when coupled to the women's age can give important signals as to the likely problem. Disorders of Menstruation follows the reproductive lifetime of women, from prepubertal abnormalities through the years of potential child bearing to menopause and beyond. The authors provide a conceptual framework to unde.
Overview : disorders of menstruation / Paul B. Marshburn and Bradley S. Hurst -- Pre-pubertal genital bleeding / Kristin M. Rager, Preeti P. Matkins, and Tara M. Vick -- Irregular vaginal bleeding and amenorrhea during pubertal years / Bradley S. Hurst -- Menstrual disorders during the reproductive years / Michelle L. Matthews -- Abnormal menstrual bleeding in hyperandrogenic ovulatory dysfunction / Rebecca S. Usadi -- Abnormal uterine bleeding due to anatomic causes : diagnosis / Bradley S. Hurst -- Abnormal uterine bleeding due to anatomic causes : treatment / Bradley S. Hurst -- Infrequent menstrual bleeding and amenorrhea during the reproductive years / Paul Miller -- Menstrual cycle related clinical disorders / Paul B. Marshburn -- Irregular uterine bleeding during the menopausal transition / Isiah Harris and William D. Schlaff -- Postmenopausal bleeding / Karen D. Bradshaw and David Tait.
Includes bibliographical references and index.
Print version record.
Keywords: Menstruation disorders; Menstruation Disturbances -- pathology; Menstrual Cycle -- physiology; Medicine; Menstruation disorders; Electronic books